Relational and Communicational Skills of Nursing Students: Results of the 1st Clinical Clerkship (Journal of Statistics on Health Decision, 2021)
Introduction:Communicational and relational skills are crucial for nursing care and are recognized as a differentiating competence of excellent care. Nursing students must develop these skills to establish an efficient helping relationship. Despite of that, studies about the efficiency of interventions to promote these skills are scarce.This study aims to evaluate the acquisition of communicational and relational skills with the first Clinical Clerkship (CCI) of the Nursing undergraduate course, in nursing students.Methods:A pilot study was conducted, before and after a CCI, which occurred during June of 2020, with a convenience sample of 37 students of the 1st year and 2nd semester of the Nursing degree Course of a health school in North of Portugal. CCI aims to develop communication skills, using innovative strategies as Portuguese sign language, dramatization, and emotional facial expression, beyond supervised care of patients in real contexts. Data collection was done using an online questionnaire composed by a sociodemographic questionnaire, the Relational and Help Skills Inventory [Inventário de Competências Relacionais e de Ajuda – ICRA] [1] and the Interpersonal Communication Assessment Scale [Escala de Avaliação da Comunicação Interpessoal - ICAS] [2,3].  Statistical analysis of this work was performed in R, accessed by RStudio, version 1.3.1093. It was used descriptive analyses and inference analysis (Wilcoxon Test), using a significance level of p